Saffordville, Chase County - Leverich, Matthew (Kansas State University, The Chapman Center for Rural Studies, 2013)
The ghost town of Saffordville, in eastern Chase County, was established in the 1870s along the Atchison, Topeka, and Santa Fe railroad. The town never incorporated, but by the early 1900s had a myriad of commercial businesses and over two hundred people. However, it was located in the flood-prone Cottonwood River valley, and when the river catastrophically flooded in 1951 the town was seriously damaged and soon abandoned. This study illustrates the history of Saffordville through newspapers, maps, photographs, and books.
Matthew Leverich, “Saffordville, Chase County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/113.
Keywords: Chase County; Saffordville; Cottonwood Falls; Emporia; Frances Staedtler; U.S. Highway 50